Comparative forensic analysis of reverse root canal filing and conventional method for DNA isolation from extracted teeth under different environmental conditions: A prospective study - Khan, Azhar Ahmed; Urs, Aadithya B; Augustine, Jeyaseelan; Singh, Hanspal (The Journal of Forensic Odonto-Stomatology - JFOS, 2020)
The grinding of a whole tooth specimen has been considered the conventional method to extract genomic deoxyribonucleic acid (DNA) in forensic science. However, we have tried the less destructive reverse root canal filing (RRCF) method without disturbing the morphology of the tooth to achieve competent amplifiable DNA. A total of 27 pairs of bilateral intact extracted teeth from the same subject were used in three different simulated environmental conditions for the respective RRCF and conventional methods: (a) soil burial for six months, (b) incineration at 200º C for 4 min, and (c) immersion in water for two months. Qualitative agarose gel electrophoresis assessment and downstream amplification were performed. The results showed significantly higher mean DNA concentration for the RRCF method in all three environmental conditions (p value = 0.008) in comparison to the conventional method. However, comparable qualitative results were found in both methods for the mean DNA concentration for incinerated (159.49 ng/ml), soil (119.52 ng/ml), and water (108.60 ng/ml) samples. It was concluded that the RRCF method is better quantitively (ng/ml) and comparable in terms of quality with respect to the conventional method, with the added advantage of preservation of the tooth morphology.